LOW RISE APARTMENT DI KOTA PONTIANAK DENGAN PENDEKATAN RESPONSIF PANDEMI - Grace Novika; Emilya Kalsum; Hamdil Khaliesh (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2022)
Massive development in almost all cities including Pontianak City has resulted in limited land. However, the demand for housing is increasing due to population growth. The residential trend is now moving into a vertical building. One of them is an apartment. Tokazhanov et al. (2020) explained that during the pandemic, 90% of cases infected with COVID-19 were in places with dense human concentrations. In Pontianak City, the Government established the Implementation of Community Activity Restrictions (PPKM) to reduce the number of COVID-19 cases, which requires people to completely change their activities at home. This makes it necessary to adapt housing to improve the quality of life of residents during the pandemic. The type of apartment designed is a low rise apartment that focuses on comfort and living experience. The design location is in Pontianak City, where economic growth is increasing, thus providing opportunities for people to buy better and more efficient housing. Low rise apartments can also accommodate businessmen who visit Pontianak City. The purpose of the design is to create a low rise apartment that can respond to the needs for security, health, and social interaction of residents during a pandemic. The design method uses the J. Christopher Jones method. The result of the design is a residential design in the form of a low rise apartment that can respond to changes in lifestyle and needs during the pandemic.